Застосування модифікованого методу лінеаризації для розв’язання нелінійних задач розподілу потоків - Kirik, H. E. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
The optimization problem of flows calculation in networks of given configuration is considered. The solution is achieved with application of combination of the first and second order linearization methods. The constructed algorithm converges from any initial approach and has the accelerated speed of convergence in comparison with the first order methods.